Yearbook of Phraseology (De Gruyter, 2010)
As the organ of the Europhras, this international yearbook is dedicated to research in phraseology, a linguistic subfield concerned with the study of word combinations of varying extent and type, and different degrees of fixedness. Their study is of interest to many other subdisciplines of linguistics, throwing light on the make-up and modes of creation of complex building blocks of language, as well as on the way in which language functions.